Farmers’ perception on the quality of agricultural extension services under the value chain development programme in Niger State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2026)
This study assessed farmers’ perceptions of the quality of agricultural extension services provided under the Value Chain Development Programme (VCDP) in Niger State, Nigeria. The specific objectives were to examine the socioeconomic characteristics of participating farmers, explore their perceptions of extension service quality, and identify the challenges they experienced during programme implementation. Data were collected through structured questionnaires from a total of 100 rice farmers who were purposively selected from two rice-producing communities each in Mokwa and Bida Local Government Areas (LGAs). These were analysed using descriptive statistics and the weighted mean score of a four-point Likert scale. Results revealed that 65% of the respondents (mean = 2.80) agreed that extension agents provide timely and relevant information, while 77% of the farmers (mean = 3.03) perceived extension agents as knowledgeable about value chain processes. Additionally, farmers reported several constraints such as poor tailoring of advisory services to local conditions (70%, mean = 2.90), high cost of credit (66%, mean = 2.82), transportation difficulties (73%, mean = 3.03), and low digital literacy (63%, mean = 2.78). The study concludes that although extension services under the VCDP are generally valued, their effectiveness is hindered by these challenges. It was recommended that government agencies, NGOs, and development partners collaborate to enhance the capacity of extension agents, improve input supply, strengthen rural infrastructure, and support digital literacy initiatives to ensure more inclusive and impactful service delivery.